Change without search? Linking performance feedback on domestic vs. export goals, near vs. distant search, and new export market entries - Bolaños Hurtado, Jean Pierre (2023)
Problemistic search argues that when companies face performance below aspirations, search for new alternatives is triggered, which ultimately drives organisational change. However, when studies test this assertion, they link performance below and above aspirations directly to observed organisational changes, omitting search as the cause for change. Yet, the process leading to change has to be proven, not assumed. To test how performance below and above aspirations triggers search and subsequent change, I hand-collected data on changes in 63930 export products and 37165 instances of export market presence from a sample of 244 Peruvian exporting firms between 2010 and 2022. I find that performance feedback faced in domestic vs. export goals yields different patterns of search for near vs. more distant export products. Once search is controlled for, performance feedback becomes less associated to change, measured as entries into new export markets. Emphasising that the search step is not trivial, I find that its effectiveness in driving change depends on the complexity of the landscape in which companies have to search.